2010
DOI: 10.2190/iq.30.2.b
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Risky Sexual Behaviors in Recently Traditionally Circumcised Men from Initiation Lodges in the Eastern Cape, South Africa

Abstract: This exploratory quantitative study examines past risky sexual behaviors among young men who were circumcised as part of a rite of passage to adulthood embedded within a cultural and traditional belief system in the Eastern Cape Province in South Africa. Following permission from the Eastern Cape House of Traditional Leaders (ECHOTL), individual face-to-face interviews using a structured questionnaire were conducted among 114 initiates. The mean age of the participants was 18.9 years, ranging from 15 to 32 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 37 publications
(39 reference statements)
0
32
0
Order By: Relevance
“…Initiated men are an important cohort to study in the context of STI/HIV prevention because of possible incorrect risk beliefs regarding the chances of HIV infection. A pilot study among recently traditional circumcised men in the Eastern Cape Province of South Africa reported that 92% of the participants believed that circumcised men do not need to use condoms during sexual intercourse [14]. A study among traditionally circumcised men in Cape Town reported that those men who were aware of the HIV preventive benefits of male circumcision and held positive beliefs about the reduced risk of HIV infection as a result of male circumcision were more likely to engage in risky sex; specifically unprotected sex and sex with multiple sexual partners [15].…”
Section: Introductionmentioning
confidence: 99%
“…Initiated men are an important cohort to study in the context of STI/HIV prevention because of possible incorrect risk beliefs regarding the chances of HIV infection. A pilot study among recently traditional circumcised men in the Eastern Cape Province of South Africa reported that 92% of the participants believed that circumcised men do not need to use condoms during sexual intercourse [14]. A study among traditionally circumcised men in Cape Town reported that those men who were aware of the HIV preventive benefits of male circumcision and held positive beliefs about the reduced risk of HIV infection as a result of male circumcision were more likely to engage in risky sex; specifically unprotected sex and sex with multiple sexual partners [15].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 48,468 participants were involved in the review, of whom 1055 and 47,413, respectively, were involved in qualitative and quantitative studies. 11 studies involved male only [62-67, 70-72, 74, 76], 7 studies involved men and women [39, 59-61, 69, 73, 75], 2 studies involved traditional circumcisers [61, 62], and 1 study involved health practitioners [61]. Participants’ ages ranged from 13 to 70 years old, however, 2 studies did not report the participant’s age [59, 63].…”
Section: Resultsmentioning
confidence: 99%
“…All questions were inspected for cultural relevance and appropriateness by community elders. The measures were piloted among 114 recently initiated and circumcised men (see Nyembezi et al, 2010). Socio-demographic questions elicited age, nation of origin ( isizwe ), whether they were currently in school (yes vs no), highest grade passed (primary, secondary or post matric), employment status (yes vs no), knowledge of local traditional leadership (yes vs no) and registration with the local chief before undergoing the initiation processes (yes vs no).…”
Section: Methodsmentioning
confidence: 99%